Mangrove Forest Health Monitoring Training at KTH Lestari Indah as a Disaster Mitigation Eﬀort - Rahmat Safe'i; Aristoteles Aristoteles; Unang Mulkhan; M. Rizky Pratama; Lis Nur Ajijah; A. Nizam Syahiib; Selvira Selvira; Annisa Putri Nabila; Risna Damayanti (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
The importance of monitoring forest health is needed to support a sustainable forest management system. A healthy forest can be said to be still carrying out its functions. Monitoring the health of mangrove forests is helpful in an eﬀort to mitigate coastal disasters. The purpose of this service was to provide knowledge and understanding to members of KTH Lestari Indah regarding forest health. This activity was carried out on Sunday, October 24, 2021, at the mangrove forest tour, Margasari Village, Labuhan Maringgai sub-district, East Lampung Regency. The methods used in this activity were lectures and practices. Based on the evaluation results with pre-test and post-test instruments given to participants regarding the material in service activities, participants experienced an increase in knowledge of 7.13%. This increase shows a reasonably good understanding of the training participants, so this training is expected to help the community increase knowledge and participation in mangrove forest management and discovery of sustainable mangrove forests.